2004
DOI: 10.1002/hyp.1408
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the distribution of snow water equivalent and snow extent beneath cloud cover in the Salt–Verde River basin, Arizona

Abstract: Abstract:The temporal and spatial continuity of spatially distributed estimates of snow-covered area (SCA) are limited by the availability of cloud-free satellite imagery; this also affects spatial estimates of snow water equivalent (SWE), as SCA can be used to define the extent of snow telemetry (SNOTEL) point SWE interpolation. In order to extend the continuity of these estimates in time and space to areas beneath the cloud cover, gridded temperature data were used to define the spatial domain of SWE interpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…For example, McGuire et al (2005) and Andreadis and Lettenmaier (2006) reported only being able to use SCA images for days where cloud obscuration was less than 20 % of the grid cell, while Rodell and Houser (2004) used 6 % as the threshold for minimum visibility. Consequently, several investigations into techniques for removing cloud cover from SCA images have been reported (e.g., Lichtenegger et al, 1981;Seidel et al, 1983;Molotch et al, 2004;Parajka and Blöschl, 2008;Gafurov and Bárdossy, 2009).…”
Section: The Problem Of Cloud Obscurationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, McGuire et al (2005) and Andreadis and Lettenmaier (2006) reported only being able to use SCA images for days where cloud obscuration was less than 20 % of the grid cell, while Rodell and Houser (2004) used 6 % as the threshold for minimum visibility. Consequently, several investigations into techniques for removing cloud cover from SCA images have been reported (e.g., Lichtenegger et al, 1981;Seidel et al, 1983;Molotch et al, 2004;Parajka and Blöschl, 2008;Gafurov and Bárdossy, 2009).…”
Section: The Problem Of Cloud Obscurationmentioning
confidence: 99%
“…Lichtenegger et al (1981) and Seidel et al (1983) used elevation, slope, exposure, and brightness information from a digital terrain model (DTM) to extrapolate snow cover from cloud-free to cloud-covered areas in digital Landsat multispectral scanner data, assuming that for each elevation zone, the regions with equivalent exposure and slope angle carry the same amount of snow. Molotch et al (2004) filtered NOHRSC SCA maps (based on AVHRR/GOES data) using gridded positive accumulated degree days (ADD) and AVHRR-derived binary SCA to obtain a threshold for defining snow cover in the Salt and Verde rivers in Arizona. They reported temperature data to be helpful for estimating snow extent beneath clouds and to thereby improve spatial and temporal continuity of SCA and SWE products.…”
Section: The Problem Of Cloud Obscurationmentioning
confidence: 99%
“…Modeling techniques include statistical approaches, such as Carroll and Cressie (1996), Elder et al (1998), Erxleben et al (2002), Anderton et al (2004), Molotch et al (2004), Dressler et al (2006), López-Moreno and Nogués-Bravo (2006), Skaugen (2007), Bavera et al (2014), and conceptual, or physically based models -e.g., Lehning et al (2006;. These works have improved our knowledge about, e.g., the relevance of single forcings in determining the distribution of snow on complex terrains (Anderton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Shimamura et al (2003) estimated SWE in a catchment by combining satellite-derived SCA with in-situ data. Molotch et al (2004) and Kazama et al (2008) successfully combined the satellite-derived SCA data with distributed snowmelt models to estimate the spatial SWE during the snowmelt season. In most research, an uncertain parameter is assumed to be constant over the catchment or other large area.…”
Section: Introductionmentioning
confidence: 99%